Factors impacting loneliness in patients with serious life-limiting illness in the Emergency Medicine Palliative Care Access (EMPallA) study - Brendan Maloney; Mara Flannery; Jason J. Bischof; Kaitlyn Van Allen; Oluwaseun Adeyemi; Keith S. Goldfeld; Allison M. Cuthel; Alex Chang; Corita R. Grudzen (BMC Palliative Care)
Abstract Background Loneliness is a quality-of-life (QoL) concern for patients facing serious, life-limiting illnesses. Discerning risk factors of loneliness in palliative care patients allows providers to take preventative action and develop holistic treatment plans. Methods A planned sub-study of patients who completed the previously developed Three-Item Loneliness Scale upon enrollment into the multicenter, randomized clinical trial Emergency Medicine Palliative Care Access (EMPallA) with the objective of investigating the association of multimorbidity with loneliness in patients with late-stage illnesses. The EMPallA study included patients who were at least 50 years old and diagnosed with at least one end-stage illness (advanced cancer, advanced congestive heart failure (CHF), end-stage renal disease (ESRD), or advanced chronic obstructive pulmonary disease (COPD)). Results We analyzed 1,212 surveys using a mixed-effects logistic regression model. Our findings suggest those with a single illness are less likely to be lonely than those with multimorbidity (odds ratio [OR] = 0.5, 95% CI 0.3 to 0.8). Additionally, older age was associated with less loneliness (OR comparing age by 10-year increments is 0.7 [95% CI: 0.6 to 0.9]), after adjusting for disease type, education level, race, sex, immigrant status, having a caregiver, COVID-19 period, language, and site geographic location. Conclusions Patients suffering from multimorbidity self-report being “very lonely” more often than patients with a single advanced illness; furthermore, advanced illness patients who were middle-aged (versus elderly) were 25% more likely to report being “very lonely.” Trial registration Clinicaltrials.gov identifier: NCT03325985. Registered October 30, 2017.